Akuntabilitas melalui Transparansi dalam Perspektif Joko Widodo - Ndaomanu, Dita Adelia; Davianti, Arthik (Perspektif Akuntansi, 2024)
This research examines the importance of accountability in central government, particularly in the context of the President of Indonesia, Joko Widodo. Accountability is the government's ability and obligation to be openly and transparently responsible for its actions and decisions. In this analysis, the research focuses on interpreting accountability through transparency according to President Joko Widodo in his state speeches using a critical discourse analysis approach. The findings indicate that President Jokowi emphasizes the importance of openness in reporting the performance of state institutions to the public, as well as transparency in conveying the government's vision and strategic steps. Jokowi also demonstrates commitments to development equality and social protection through implemented policies. Thus, President Jokowi's perspective on accountability provides valuable insights into the practice of accountability and government policies in Indonesia during his leadership. This research highlights the importance of openness and tangible actions in strengthening a leader's position as an accountable and transparent agent in governance.